The A to G transition at nt 3243 of the mitochondrial tRNALeu(UUR) may cause an MERRF syndrome. Issue 1 (July 1996) - Fabrizi, G M; Cardaioli, E; Grieco, G S; Cavallaro, T; Malandrini, A; Manneschi, L; Dotti, M T; Federico, A; Guazzi, G
Abstract : OBJECTIVE--To verify the phenotype to genotype correlations of mitochondrial DNA (mtDNA) related disorders in an atypical maternally inherited encephalomyopathy. METHODS--Neuroradiological, morphological, biochemical, and molecular genetic analyses were performed on the affected members of a pedigree harbouring the heteroplasmic A to G transition at nucleotide 3243 of the mitochondrial tRNALeu(UUR), which is usually associated with the syndrome of mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS). RESULTS--The proband was affected by a fullblown syndrome of myoclonic epilepsy with ragged red fibres (MERRF), severe brain atrophy, and basal ganglia calcifications, without the MRI T2 hyperintense focal lesions which are pathognomonic of MELAS. Oligosymptomatic relatives were variably affected by lipomas, goitre, brain atrophy, and basal ganglia calcifications. Muscle biopsies in the proband and his mother showed a MELAS-like pattern with cytochrome c oxidase hyperreactive ragged red fibres and strongly succinate dehydrogenase reactive vessels. Quantification of the A3243G mutation disclosed 78% and 70% of mutated mtDNA in the muscle of the severely affected proband and of his oligosymptomatic mother respectively. Nucleotide sequencing of the mitochondrial tRNALeu(UUR) and tRNALys in the proband's muscle failed to show any additional nucleotide change which could account for the clinical oddity of this pedigree by modulating the expression of the primary pathogenic mutation. CONCLUSION--So far, MERRF has been associated with mutations of the mitochondrial tRNALys, and MELAS with mutations of the mitochondrial tRNALeu(UUR). Now MERRF may also be considered among the clinical syndromes associated with the A to G transition at nt 3243 of the tRNALeu(UUR).